Verbal problems of equitable redistribution in kindergarten (Edma 0-6: Educación Matemática en la Infancia, 2021)
This research proposes a workshop on arithmetic problems in early childhood education, composed by eight problems, introducing two problems of equitable sharing of several steps for children of 5-6 years old. It aims to know if the students of these ages are capable of solving problems through manipulation and observing the strategies that children use. The problems of equitable sharing start with two quantities, one bigger than other and children have to get out even out quantities so both have the same amount without adding any external counters. The unknown in the first problem posed is the quantity to form even quantities and in the second problem solving is the quantity of counters that need to be transferred from the group with more objects to the group with less. Children solved the problems using direct modeling strategies of redistribution.
Keywords: Early Childhood (Kindergarten); Problem solving; Direct modelling; Strategies of redistribution; Problems of equitable sharing